The Memory of Feeling: Envy and Happiness - Hamman, Jaco J. (Pastoral psychology, 2015)
This essay explores how happiness is maintained as a memory of the first relationship and when that memory is disturbed, envy can set in. Envy is the angry feeling that another person possesses and enjoys something desirable-the envious impulse being to take it away or to spoil it. The thought of Melanie Klein and her 1957 work, Envy and Gratitude, guides the inquiry. Happiness in one person can offend when another experiences the happiness as goodness of life that is being withheld from them. Since all persons carry the memory of happiness, seeing the happiness of others reminds us of something once owned or experienced, but now lost. Envy becomes a defense against the painful memory of happiness once known. The biblical figure King Saul is identified as someone who experienced envy in the face of a young David's happiness. Envy not only robs a person of happiness, it removes a sense of gratitude.